Plant-Derived Exosomes as Emerging Therapeutics in Prostate Cancer: A Multifunctional Nanobiotechnology Approach - Dincer, Zeynep Yaren; Ziksahna, Kaan; Ozkan, Melisa; Ihlamur, Murat (SPRINGERNATURE, 2026)
BackgroundPlant-derived extracellular vesicles (PDEVs) (often referred to in this review as 'plant-derived exosomes') have recently emerged as promising nanocarriers with intrinsic therapeutic potential. Their biocompatibility, scalability, and phytochemical cargo distinguish them from mammalian exosomes and synthetic nanocarriers. While PDEVs have been studied across various cancers, their applications in prostate cancer-a disease characterized by therapy resistance, inflammation, and metastatic progression-remain underexplored.ObjectiveThis review summarizes current knowledge on PDEVs with a specific focus on their anticancer potential in prostate cancer.MethodsLiterature from PubMed, Web of Science, and Scopus was critically reviewed, emphasizing studies on PDEVs in cancer models, with attention to prostate cancer-related evidence.ResultsPDEVs can induce apoptosis, suppress proliferation, modulate immune responses, and inhibit metastatic processes. Ginger, grape, green tea, garlic, apple, aloe vera, and pomegranate exosomes carry bioactive compounds such as polyphenols and flavonoids that exert antitumor effects. In prostate cancer, these mechanisms are particularly relevant for overcoming androgen receptor-driven proliferation, suppressing chronic inflammation, and preventing bone metastases. PDEVs also hold promise as delivery vehicles for prostate-targeted strategies, including PSMA-directed therapies and AR-silencing siRNAs.ConclusionsPDEVs represent a dual-function platform-providing intrinsic anticancer activity and serving as natural nanocarriers. Their novelty in prostate cancer lies in the ability to combine phytochemical activity with targeted drug delivery. Future directions include engineering PDEVs for prostate-specific delivery and testing them in robust preclinical and clinical models. Despite encouraging findings, the absence of prostate cancer-specific animal models and clinical trials remains a major translational barrier.
Keywords: Plant-derived exosomes; Prostate cancer; Apoptosis; Immunomodulation; Targeted drug delivery; NANOVESICLES; DELIVERY; GINGER; CELLS; NANOPARTICLES; RESISTANCE; VESICLES; COLITIS; DAMAGE; TEA; General & Internal Medicine